The Psychodynamic Overview of Generalized Anxiety Disorder in Young Adults - Prasetya, Era Catur; Lestari , Rizky Dwi; Mahyuddin, Muhammad Hanun; Haniifah, Ulaa; Atsira, Olga (UNUSA Press, 2023)
The Diagnostic and Statistical Manual of Mental Disorders (DSM-5) defines an anxiety disorder as an excessive feeling of fear that occurs in a person that interferes with daily activities. Generalized anxiety disorder causes a person to feel anxious about a wide range of situations and issues. Patients often experience anxiety, feelings of fear and constantly on edge, difficulty concentrating, difficulty sleeping, muscle tension, and frequent irritability. Based on data from the Indonesian Ministry of Health in 2007, there were 450 million people who had to live with mental disorders. The prevalence of adult individuals (aged 18 years and over) and the elderly, there were 11.6% who experienced emotional disorders, such as anxiety and depression. This case report discusses a 20-year-old woman with the main complaint of unclear anxiety, not knowing what to worry about, floating between things she worries about is death, fear of having a serious illness, breakup, fear of losing her job as a content creator, and feeling of being blamed that keeps on coming. Management in the form of giving SSRI antidepressants and psychodynamic psychotherapy is done to try to reinterpret feelings of guilt that often arise as a result of fixation in one phase of their growth and development.